PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM COOPERATIVE LEARNING DALAM PEMBELAJARAN BAHASA ARAB DI SD IT AZIZAH PALEMBANG - Hafizah Adilah; Jumhur; Nazarmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the condition of Arabic language learning at Azizah Integrated Islamic Elementary School in Palembang, which still employs traditional methods (lecturing, question-and-answer, and direct method). These methods tend to be monotonous and lack creativity, resulting in students showing minimal enthusiasm, possessing passive vocabulary mastery, and facing difficulties in comprehensively using Arabic in their daily lives. Therefore, this study aims to test the effectiveness of combining innovative learning models, namely the Flipped Classroom and Cooperative Learning, to enhance the quality of Arabic language instruction. The specific objectives of this research are to determine the process of Arabic language learning both before and after the application of these models, and to measure the level of their effectiveness. This study employs a mixed methods approach. The quantitative approach utilizes a quasi-experimental design with a pretest-posttest structure to assess the model's impact on learning outcomes. Meanwhile, the qualitative approach (observation and interviews) is used to explore the learning process and students' experiences. The independent variable (X) is the Flipped Classroom and Cooperative Learning model, and the dependent variable (Y) is the students' learning outcomes. The research findings indicate that before the application, learning in the fifth grade was traditional, leading to a lack of variation and student enthusiasm. Following the implementation of the Flipped Classroom and Cooperative Learning models, the learning process became more structured and active. Students independently studied materials (videos and digital resources) at home first, and subsequently deepened their understanding in class through collaborative group activities (discussions, dialogue practice, text reading, and simple sentence writing). The application of this integrated model successfully increased participation, initiative, and enthusiasm. Overall, the Flipped Classroom and Cooperative Learning models proved to be effective in improving Arabic language learning outcomes for fifth-grade students at Azizah Integrated Islamic Elementary School in Palembang.